2010
DOI: 10.1146/annurev.publhealth.012809.103639
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Symposium on Public Health Significance of Genomics and Eco-Genetics

Abstract: Genomic and genetic information is rapidly becoming a major element in public health research and emerging public health practice. This symposium reviews the methods, findings, and significance of genomewide association studies from epidemiological and statistical points of view. We examine infectious and inflammatory components of geneenvironment interaction in the respiratory system. We note the need for nutrient and dietary data and many other kinds of environmental exposure data in population-based genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…17,18 Family history obtains risk information concerning these shared environmental factors and genetics. 10 One study that explored perceptions of family history found increased perceived risk and worry among those with a family history of diabetes and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Family history obtains risk information concerning these shared environmental factors and genetics. 10 One study that explored perceptions of family history found increased perceived risk and worry among those with a family history of diabetes and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Why? Because their effects are moderated via gene x gene and gene x environment interactions, whose effects are counted in estimates of broad heritability [114]. High heritability does not imply that specific alleles or combinations of alleles will predict the phenotype.…”
Section: From Evolutionary Medicine To Evolutionary Molecular Medicinementioning
confidence: 99%
“…Currently, health promotion programs utilize primary preventative measures such as exercise, diet, weight loss, and stress management [20]. Additionally, clinical indicators and risk factors such as blood pressure, glucose, and lipids are being incorporated into screening, and the potential value of combining these with large-scale genomic and molecular measurements have been discussed [21] but not yet assessed in the context of health promotion. Further, use of these measures is on the 10-year agenda for the United States Department of Health and Human Services Healthy People 2020 health promotion program [22].…”
Section: Introductionmentioning
confidence: 99%